Implementasi System Usability Scale untuk Pengujian Usabilitas Chronum Calculator - Febria Sri Handayani; Dini Hari Pertiwi; Yesi Sriyeni (UNIVERSITAS INDO GLOBAL MANDIRI)
Chronum Calculator is an alternative learning aid developed to support learning about number conversion. Chronum Calculator is a multimedia learning application that can be used to calculate and describe how to calculate the conversion between types of numbers and the conversion of numbers into color display. In previous research, this application was developed on the Android platform and is planned to be used as a learning aid in computer network and computer organization courses. Therefore, reusability test of this application is needed. Testing and measuring the quality of application reusability is done using the System Usability Scale (SUS) method. The reusability testing questionnaire was given to 31 samples of lecturers and students. The measurement result shows the number 76.38 and is considered acceptable. Where this means that the Chronum Calculator can be well received by users and meets application reusability standards. The results of this research can be used as a basis for further research on the analysis of the effect of usability on user satisfaction chronum calculators in online lectures. Keywords : Android, SUS, Usability, Respondents, Measuring